The Role of High and Low Testosterone Levels in the Development of Cardiovascular Pathology (on the Example of Clinical Cases) - Timofeev, E.V.; Petrova, E.A.; Reeva, S.V.; Parfenova, N.N. (Juvenis Scientia)
A decrease and increase in testosterone levels in men before andropause is accompanied by a number of metabolic, functional and organic changes on the part of various systems, primarily the cardiovascular system. Such men are characterized by the development of dyslipidemia and increased cardiovascular risk. Hypogonadism is also associated with obesity, impaired carbohydrate metabolism, and the development of atherosclerosis. Uncontrolled administration of anabolic steroid hormones in the absence of medical indications for this leads to impaired blood rheology, the development of life-threatening cardiac arrhythmias, severe heart failure, and intravascular thrombosis. Two clinical cases are presented: a young man with an arrhythmic variant of cardiomyopathy, which developed as a result of taking anabolic steroids, and a middle-aged man with long-term existing hypogonadism. The clinical manifestations of these conditions, the rate of their development and progression, and the reaction of changes to hormone replacement and non-specific therapy performed in the case of hypogonadism are shown. The peculiarities of both cases are that the patients themselves underestimate the severity of the changes and their condition, and refuse to correct therapy. Despite the obvious and simple treatment of such conditions and the reversibility of most changes, low adherence to therapy significantly increases cardiovascular risk and the risk of sudden death.